THE OCCURRENCE OF METHANE GAS SEEPAGES IN THE UPPER KETUNGAU AREA, WEST KALIMANTAN - Hermes Panggabean (Indonesian Mining Journal, 2005)
Uplifting event on the Boyan Melange, that formerly known as the Semitau High in West Kalimantan has resulted in the separated Ketungau and Melawi Basins in the Late Cretaceous or Early Tertiary time. Initial stage of sedimentary deposition within the Ketungau Basin occurred in Early Eocene, depositing a fluvial conglomerate unit that subsequently changes upwards into a shallow marine and lacustrine unit of the Kantu Formation. The Eocene Kantu Formation consists of alternating dark grey and laminated carbonaceous shale, mudstone and siltstone with coal seam intercalations and the Ketungau Formation, which is composed of alternating dark grey and laminated carbonaceous shale, claystone, siltstone with coal seam intercalations inferred to be able performed as a source rocks for initial biogenic methane. On the other hand, the Oligo-Miocene Tutoop Sandstone that consists of dominantly a coarse- to fine-grained clastic unit may potentially conduct as a secondary reservoir rock for coalbed methane. Gas seepages that have been observed on surface along the tributary of Peturau and Sebuntung Rivers in the Upper Ketungau region is presumed to be derived from a coalbed methane source within the Kantu and Ketungau Formations. The methane gas is assummed to be ascending on surface through structural faults that trending NW-SE direction.